Privacy and identity management for the future internet in the age of globalisation : 9th IFIP WG 9.2, 9.5, 9.6/11.7, 11.4, 11.6/SIG 9.2.2 International Summer School, Patras, Greece, September 7-12, 2014, Revised selected papers /: 9th IFIP WG 9.2, 9.5, 9.6/11.7, 11.4, 11.6/SIG 9.2.2 International Summer School, Patras, Greece, September 7-12, 2014, Revised selected papers. (2015) - Unknown
No abstract available